Babesia Species of Domestic Cats: Molecular Characterization Has Opened Pandora's Box - Penzhorn, Barend L.; Oosthuizen, Marinda C. (Frontiers in Veterinary Science, 2020)
This is the first comprehensive review of the literature pertaining to Babesia spp. reported from domestic cats. Description of the four species (B. felis, B. cati, B. herpailuri and B. pantherae) named based on morphology and/or host-specificity is documented. Feline babesiosis is of major veterinary concern only in South Africa. Reports of the rare occurrence of feline babesiosis cases in Europe (France, Germany, Poland and Spain) and Asia (Israel, India and Pakistan) are documented. Molecular characterisation has revealed that cats can harbour a variety of Babesia spp. The previous practice of referring to all piroplasms, especially small ones, seen on feline blood smears as B. felis is therefore no longer tenable. The near-full-length 18S rRNA gene sequences entered into GenBank in 2001 (accession number AF244912) are designated as definitive for B. felis sensu stricto. All published literature relating to molecular characterisation of feline Babesia species that could be traced was critically assessed. Four Babesia spp. are now known to be involved in causing feline babesiosis in South Africa: the closely related B. felis s.s. and B. leo (Clade I), B. lengau (Clade II) and Babesia sp. cat Western Cape (clade VI, Babesia s.s.). Clade VI also includes B. canis presentii and B. hongkongensis reported from cats in Asia. Six other Babesia spp. have been reported from domestic cats: the dog-associated B. canis s.s., B. gibsoni and B. vogeli, as well as B. lohae, B. microti and B. vulpes. Phylogenetic relationships of all named species were assessed and are presented as trees. The relatively high prevalence of B. vogeli in clinically healthy cats (16% in Brazil, 13% on St Kitts and 8.1% in Portugal) suggests that immunocompetent cats can harbour the infection with no discernible untoward effects. Reports of occurrence of B. felis and other Babesia spp. in domestic cats should be accepted only if they are supported by credible molecular provenance.